Stationary distribution of stochastic SIS epidemic model with vaccination under regime switching. (September 2016) - Zhang, Xinhong; Jiang, Daqing; Alsaedi, Ahmed; Hayat, Tasawar
Abstract: This paper addresses a stochastic SIS epidemic model with vaccination under regime switching. The stochastic model in this paper includes white and color noises. By constructing stochastic Lyapunov functions with regime switching, we establish sufficient conditions for the existence of a unique ergodic stationary distribution.